2022
DOI: 10.1038/s41598-022-22444-1
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing of LiNi1/3Mn1/3Co1/3O2 battery electrode material via vat photopolymerization precursor approach

Abstract: Additive manufacturing, also called 3D printing, has the potential to enable the development of flexible, wearable and customizable batteries of any shape, maximizing energy storage while also reducing dead-weight and volume. In this work, for the first time, three-dimensional complex electrode structures of high-energy density LiNi1/3Mn1/3Co1/3O2 (NMC 111) material are developed by means of a vat photopolymerization (VPP) process combined with an innovative precursor approach. This innovative approach involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
0
9
1
Order By: Relevance
“…And in 3D‐printed cells using various space filling [ 35 ] and fractal geometries, the infilling of active material that is accessible and without excessive internal resistance is important for a reliable cell. Here have been recent reports of Vat‐P printing [ 24,26 ] of electrodes with active materials directly within the resins where resin‐soluble precursors approaches are used, and this shows the sensitive relationship between the printed material quality and the mechanical properties. This trade‐off can render directly printed materials, in some case, to be brittle particularly when porous.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And in 3D‐printed cells using various space filling [ 35 ] and fractal geometries, the infilling of active material that is accessible and without excessive internal resistance is important for a reliable cell. Here have been recent reports of Vat‐P printing [ 24,26 ] of electrodes with active materials directly within the resins where resin‐soluble precursors approaches are used, and this shows the sensitive relationship between the printed material quality and the mechanical properties. This trade‐off can render directly printed materials, in some case, to be brittle particularly when porous.…”
Section: Resultsmentioning
confidence: 99%
“…That work also highlighted the potential of SLA‐based printing for constructing an ultrathin and mechanical robust lithium‐ion battery (LIB). More recently, Martinez et al showed [ 26 ] that Vat‐P can be used to directly print battery electrodes containing LiNi 1/3 Mn 1/3 Co 1/3 O 2 (NMC 111) by carefully choosing the precursor and accommodating changes to light scattering in the composite resin to ensure good print quality.…”
Section: Introductionmentioning
confidence: 99%
“…As part of the efforts for SIBs manufacturing, researchers are exploring additive manufacturing (also called 3D printing) as an efficient manufacturing tool to produce on-demand 3D batteries [9][10][11][12][13]. With all commercial batteries being composed of an anode and a cathode separated by an electrolyte in a 2D stacked arrangement, 3D printing has the potential to revolutionize the manufacturing of batteries by allowing the production of complex and detailed structures, which can serve as energy storage devices and potentially as load-bearing structures [14]. From the battery performance standpoint, 3D printing can revolutionize the production of shape-conformable SIBs as a dramatic increase in the electrode's surface area and ion diffusion in three dimensions theoretically lead to improved power performance [15].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of an adequate plasticizer into the filament is critical to allow the introduction of a high loading of active material and conductive additives . Other additive manufacturing technologies, namely vat photopolymerization (VPP) , and powder bed fusion (PBF), , have been recently employed to print battery components. A VPP printer is fed with a liquid photocurable resin, employed as material feedstock, and selectively exposed to a UV light to build 3D structures.…”
mentioning
confidence: 99%